The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1002/jemt.24443
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of foliar epidermal anatomical traits and their taxonomic relevance in Lilium pumilum, L. brownii, and L. davidi

Qiaorui Ba,
Wajid Khan,
Jianwen Pang
et al.

Abstract: The anatomical traits of plant species are essential for taxonomic analyses and evolutionary evaluations. Clarifying the anatomical characteristics of the foliar epidermis in three distinct Lilium species L. pumilum Delile, L. brownii F.E.Br. ex Miellez and L. davidii Duch. ex Elwes were studied in this article. The objective is to assess the taxonomic relevance of these characteristics and their potential as indicators of species divergence within the genus Lilium. Plant samples were gathered in Gansu, China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The specific measurements of L. rosthornii stomata can be compared with findings from other Lilium species to assess whether they are unique adaptations to this species' particular ecological niche or common traits shared across the genus. For instance, a study on the diverse ploidy levels across the genus Lilium could provide insight into how these genetic variations might affect stomatal size and, consequently, the plant's adaptation to different environments (Ba et al, 2024; Yembaturova & Korchagina, 2010). Leaf thickness is another important variable in plant adaptation, contributing to structural support and influencing photosynthetic capacity (Tian et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The specific measurements of L. rosthornii stomata can be compared with findings from other Lilium species to assess whether they are unique adaptations to this species' particular ecological niche or common traits shared across the genus. For instance, a study on the diverse ploidy levels across the genus Lilium could provide insight into how these genetic variations might affect stomatal size and, consequently, the plant's adaptation to different environments (Ba et al, 2024; Yembaturova & Korchagina, 2010). Leaf thickness is another important variable in plant adaptation, contributing to structural support and influencing photosynthetic capacity (Tian et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The approach used in this work is similar to that utilized in prior investigations of foliar epidermal anatomy, such as the comparative examination of foliar epidermal anatomical characteristics in L. pumilum, L. brownii , and L. davidi (Ba et al, 2024) Numerous studies have shown the significance of the anatomical characteristics of the foliar epidermis in the context of taxonomy analysis and evolutionary assessments. An in‐depth examination of the foliar epidermal structure of L. rosthornii enhances our understanding of this species and its taxonomic and evolutionary implications.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations